EKSPERIMEN PERFORMANCE POMPA AIR DENGAN PENGATURAN SUCTION HEAD - M.Si, Drs. INDARTONO M.Par (Universitas Diponegoro, 2012)
The study objectives were: (1). to determine the efficiency of the pump with high and low suction head setting. (2). to know the power consumption saving. (3). To determine pump performance that is widely used by the public. This research was conducted at the Laboratory of Mechanical Engineering, D III Programme, Faculty of Engineering, Diponegoro University. The study took 3 (three) of about 6 (six) pump brands as a sample which is traded and used by the public in Semarang. Water flow and electric current data are calculated to determine the pump efficiency data, then analyzed using analysis of variance statistical methods with formula , Mk brands is the mean squared of brands, Mk suction head is the mean square of the suction head, and Mk Dal is the inner mean square. Data analysis result showed that for the suction head with degrees of freedom 22 versus 10, null approach limit is 2.3 at significance level of 5% and 3.26 at significance level of 1%. Thus the hypothesis can not be defended (rejected) because the value of the F from table are far away from generated F. As for inter-brand, with degrees of freedom of 22 versus 2 hypothesis rejection limit is 3.44 for 5% significance level and 5.72 for the 1% level. The result show that for inter-brand, the generated Fo is much larger than Ft,, so the hypothesis are acceptable, it is proved that there is a difference in pump performance and efficiency between one and another pump brands. Installation of pumps will be efficient when the distance of suction head is relatively small and based on the test, Fuji’s pump brand is better than the other 2 (two) pumps. Keywords: Water Pumps, Suction Head and Efficiency